Influence of Technology on the Study Habits of Students at RAK Medical and Health Sciences University - Zaidi, Dr. Huma; Abd El Kader, Dr. Rabab; David, Ms. Sheeba; Rahman, Dr. Abeer Sharmeen; Bhat, Dr. Raghavendra (International Journal of Innovative Research in Medical Science, 2019)
This study examined how technology influences the study habits of students at RAK Medical and Health Sciences University. A cross sectional survey was conducted among 306 health sciences students using a self-administered questionnaire about their study habits (preparation for exam, place of study, use of text books / online study, device used, time spent on technology) and use of technology. The results showed that students rely more on technology than text books to study. Further studies can be conducted to investigate how technology can be used to improve their psychomotor and linguistic skills including communication skills which are vital for health care professionals.